ANALISIS PELAYANAN COUNTER CHECK-IN CITILINK INDONESIA DENGAN MENGGUNAKAN METODE ANTRIAN DI ERA PANDEMI COVID-19 - Nugraha, Yudha Eka; Hau, Yurisah Adiningsih (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021), 2021)
Tourism as one of the priority sectors that is developing in Indonesia has an impact on increasing number of air travelers in Indonesia. Air travel actors consist of various elements, one of which is tourists. During air travel, tourists need to go through the check-in process at the airport before they arrived in destination. This study aims to analyze the punctuality of the check-in counter service of Citilink Indonesia airline at Ground Handling company in PT Gapura Angkasa using the queuing theory and FIFO. Counter check-in services will refer to Ministerial Regulation Number 38, 2015. The quantitative descriptive method was chosen as the approach to this research. Services at Citilink Indonesia's check-in counters are analyzed using the multiple line queuing theory. In calculating the data, the queue observation is calculated, the queue time is recorded, and is equipped with an interview with the check-in counter frontliner. Based on the research results, Citilink Indonesia's counter check-in service at El-Tari Kupang Airport shows that: 1) The waiting time for air travelers in the queue is <20 minutes. 2) Service time for air travelers at the counter check at Citilink Indonesia per person is <2 minutes 30 seconds. The results of this study conclude that the Citilink Indonesia counter check-in service at El-Tari Airport, Kupang is in accordance with Ministerial Direction No. 38 of 2015. According to the result given, Check In Counter Citilink Indonesa has always been commited to give the best service quality for passenger, and obey health protocol while check-in process happens.